Cucurbitacin B inhibits proliferation, induces G2/M cycle arrest and autophagy without affecting apoptosis but enhances MTT reduction in PC12 cells (Bangladesh Journal of Pharmacology, 2015)
In the present study, the effect of cucurbitacin B (a natural product with anti-cancer effect) was studied on PC12 cells. It significantly reduced the cell number, changed cell morphology and inhibited colony formation while MTT results showed increased cell viability. Cucurbitacin B treatment increased activity of succinode hydrogenase. No alteration in the integrity of mem-brane, the release of lactic dehydrogenase, the mitochondrial membrane potential, and the expression of apoptotic proteins suggested that cucurbitacin B did not induce apoptosis. The cell cycle was remarkably arrested at G2/M phase. Furthermore, cucurbitacin B induced autophagy as evidence by accumulation of autophagic vacuoles and the increase of LC3II. In addition, cucurbitacin B up-regulated the expression of p-beclin-1, p-ULK1, p-Wee1, p21 and down-regulated p-mTOR, p-p70S6K, CDC25C, CDK1, Cyclin B1. In conclusion, cucurbitacin B inhibited PC12 proliferation but caused MTT pitfall. Cucurbitacin B induced G2/M cell cycle arrest, autophagy, but not the apoptosis in PC12 cells.